Facts and legends about the burning of Washington, D.C. in 1814 - Daszyńska, Jolanta A. (City and War, 2021)
Federal City as Washington, D.C. was called was a symbol for Americans. It was both the capital and a symbol of new federal power. It was indicated on map in 1790 and within ten years be ready to start. In retaliation for the Americans’ recent burning of the Canadian capital at York (Toronto), British troops descended on Washington, D.C. On August 24, 1814 they entered the city. At night they torched the Capitol, the President’s Mansion and nearly every other public buildings. Washington, D.C. was burning for 26 hours. Suddenly a huge storm and an accompanying tornado, although still destructive, actually helped save the American capital from further occupation and destruction by British troops. The storm became known as „Storm that Saved Washington”.